2014
DOI: 10.3168/jds.2014-7939
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Brix refractometer to estimate serum immunoglobulin G concentration in neonatal dairy calves

Abstract: The objective of this study was to evaluate the utility of a digital Brix refractometer for the assessment of success of passive transfer of maternal immunoglobulin compared with the measurement of serum total protein (STP) by refractometry. Blood samples (n = 400) were collected from calves at 3 to 6d of age. Serum IgG concentration was determined by radial immunodiffusion (RID), and STP and percentage Brix (%Brix) were determined using a digital refractometer. The mean IgG concentration was 24.1g/L [standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
163
5
17

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(209 citation statements)
references
References 15 publications
24
163
5
17
Order By: Relevance
“…Its advantages were previously described by Wallace et al [42] who reported that the results of refractometry from centrifuge-and noncentrifugeharvested sources of serum were highly correlated so producers can conduct this test on-farm without the need of a centrifuge. Similar to results of Deelen et al [41], our results showed that % Brix highly correlated with the concentration of serum IgG, when all calves where considered, independently of the serum IgG concentration. This result undoubtedly showed that Brix refractometry can be used for assessing FPT.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Its advantages were previously described by Wallace et al [42] who reported that the results of refractometry from centrifuge-and noncentrifugeharvested sources of serum were highly correlated so producers can conduct this test on-farm without the need of a centrifuge. Similar to results of Deelen et al [41], our results showed that % Brix highly correlated with the concentration of serum IgG, when all calves where considered, independently of the serum IgG concentration. This result undoubtedly showed that Brix refractometry can be used for assessing FPT.…”
Section: Discussionsupporting
confidence: 81%
“…This result undoubtedly showed that Brix refractometry can be used for assessing FPT. Also, similar to Deelen et al [41] we found a correlation between % Brix and total serum proteins when all sera were included in the calculation. However, when we analyzed sera of calves with FPT (<10 g/L IgG) we did not fi nd a signifi cant correlation between % Brix and the concentration of total serum proteins.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In comparison, these values are higher than those reported previously for counterpart TIR-based assays for equid IgG 21,32 and camelid IgG levels, 3 and for the ATR-IR method described for canine IgG concentrations. 40 Furthermore, the correlation coefficients between IgG concentrations predicted by both IR spectroscopic methods and the reference RID IgG assay were higher than those reported for refractometry, 9,28 similar to those of near-IR spectroscopy, 52 but lower than the value reported for automated turbidimetric immunoassay. 1 The level of agreement between results from the 2 IR spectroscopic methods and the RID assay for detecting FPTI was high, as assessed using kappa statistics (Table 2).…”
Section: Discussionmentioning
confidence: 66%
“…A way to evaluate the efficiency of the supply of colostrum R. Bras. Zootec., 44(10): [361][362][363][364][365][366][367][368][369][370]2015 is by monitoring the serum protein of newborns by using a refractometer of brix or of protein (Deelen et al, 2014). These tools have a very low cost, even though 98% of producers did not monitor the serum protein.…”
Section: Resultsmentioning
confidence: 99%